A STUDY OF NHA TRANG BAY MARINE PROTECTED AREA’S MANAGEMENT EFFECTIVENESS - Anh, Nguyen Thi Kim; Khanh, Tran (Vietnam Journal of Marine Science and Technology, 2009)
The Nha Trang Bay Marine Protected Area (MPA) was established since 2002. Its objective is “To protect marine biodiversity environment and to enable local island communities to improve their livelihoods and in partnership with other stakeholders to effectively protect and manage the marine biodiversity in Nha Trang Bay as a model for collaborative MPA management in Vietnam.” After a period of operating, to consider whether the Nha Trang Bay MPA achieves the objectives, a study of Nha Trang bay MPA’s management effectiveness has been developed. With the associating of 3 study methods: taking expert advice, social survey and descriptive statistics, the authors have investgated 4 island villages: Bich Dam, Vung Ngan, Hon Mot and Dam Bay through face to face and deep interviews in the end of 2008. The results show that with the objective to protect marine biodiversity, the MPA has been done well. However, the other objective to enable local island communities to improve their livelihoods has fallen short of its expectations.